Application of Polyaniline as an Adsorbent and a Photocatalyst for the Removal of Parabens from Wastewater - Correia, Teresa Vitória Barreto Chichorro Cabral (2024)
Dissertação de Mestrado em Engenharia Química apresentada à Faculdade de Ciências e Tecnologia